Frequently Asked Questions about Vibrio in Florida - Gabby Barbarite; Peter J. McCarthy; Holly Abeels; Anita Wright (EDIS)
Florida is a tropical paradise that attracts marine enthusiasts and seafood lovers from around the world. Its extensive waterways not only offer unique areas for us to explore but also provide essential habitat for marine life, including marine bacteria that keep the habitat in healthy balance by breaking down organic matter and providing food for larger organisms. One type of marine bacteria known as Vibrio sometimes causes infections and seafood sickness in people with weakened immune systems, but Vibrio should not keep Floridians and visitors from enjoying their favorite activities because Vibrio infections are rare and easy to prevent. This 7-page fact sheet will help you ensure that your time on the water is as safe and enjoyable as possible. Written by Gabby Barbarite, Peter J. McCarthy, Holly Abeels, and Anita Wrightwill, and published by the Florida Sea Grant College Program, November 2015.